EFFECT OF EXPERIENCE IN BUILDING SATISFACTION, TRUST AND LOYALTY - Pramita, Putu Eny Guna (Universitas Brawijaya, Indonesia, 2019)
The purpose of this study is to explain the effect of experience on satisfaction, trust and loyalty. This study was conducted on inpatients service users in RSIA Puri Bunda Denpasar with a total of 100 respondents. Data analyzed with Partial Least Square technique. The results showed that experience, satisfaction and trust had a positive and significant effect on loyalty, experience had a positive and significant effect on satisfaction and experience had a positive and significant effect on trust. The implications of this study can be used as the basis for the management of the hospital to improve services and facilities, gathering and handling complaints to provide a good experience so that impact on patient loyalty. Suggestions for future research is to complement and enrich empirical studies related to this topic using other variables. Future research also needs to enrich empirical studies using other subjects and even other research locations. And with the technique of determining samples in addition to purposive sampling, for example, random sampling techniques.